2018
DOI: 10.3174/ajnr.a5714
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Gadolinium Enhancement of Skull Base Chordomas

Abstract: Enhancement of skull base chordomas is a risk factor for tumor progression/recurrence following surgical resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Chordoma is frequently hyperintense on T2-weighted imaging with hypointense septations and small foci of hypointensity corresponding to hemorrhage, calcification and mucus pooling [ 56 , 57 ]. Most chordomas will enhance moderately-to-intensely with gadolinium in a variable “honeycomb” pattern and some studies suggest that the degree of contrast enhancement correlates with aggressive tumor behavior and risk of recurrence/progression after surgical resection [ 58 ].…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Chordoma is frequently hyperintense on T2-weighted imaging with hypointense septations and small foci of hypointensity corresponding to hemorrhage, calcification and mucus pooling [ 56 , 57 ]. Most chordomas will enhance moderately-to-intensely with gadolinium in a variable “honeycomb” pattern and some studies suggest that the degree of contrast enhancement correlates with aggressive tumor behavior and risk of recurrence/progression after surgical resection [ 58 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Four subtypes of chordoma are currently recognized: conventional (which is the most common), chondroid (in which areas mimicking hyaline or myxoid cartilage are seen), poorly differentiated and dedifferentiated or sarcomatoid chordoma (chordoma associated with a high-grade sarcoma, which accounts for only 5% of cases and confers the worst prognosis) [ 2 , 58 , 59 , 60 ]. Because chondroid chordomas share pathological features with chondrosarcoma and because their clinical presentation and radiographic appearance are often similar, distinguishing between the two histologically may be challenging.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…With MR imaging analysis, the sampling error is greatly reduced because ROIs are selected by drawing the largest possible elliptic area within the tumor but avoiding areas of hemorrhage, necrosis, cyst, or calcification. 15,17,25 This feature may also indicate the emergence of new malignant cell populations within the recurrent tumor when the MRT tumors recurred as CDT tumors in some cases. Additionally, we found that most of the tumors that underwent multiple resections eventually evolved into CDTs (10/14) (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Recent studies have suggested that MR imaging signal intensity ratios on different sequences (ratio of tumor-to-pons signal intensity on T1 FLAIR [R T1 ]; ratio of tumor-to-pons signal intensity on T2 [R T2 ]; ratio of tumor-to-pons signal intensity on enhanced T1 FLAIR [R EN ]) are useful in predicting outcomes. Tian et al 16 revealed that higher R T2 predicted diminished tumor progression and higher R EN predicted more rapid tumor progression; this correlation between R EN and recurrence or progression was also shown by Lin et al 17 However, neither of these studies showed evidence for the possible explanation of signal intensity difference.…”
mentioning
confidence: 80%